Ecological controls of mammalian diversification vary with phylogenetic scale. Issue 1 (27th October 2017) - Machac, Antonin; Graham, Catherine H.; Storch, David
Abstract: Aim: Diversity dynamics remain controversial. Here, we examine these dynamics, together with the ecological factors governing them, across mammalian clades of different ages and sizes, representing different phylogenetic scales. Specifically, we investigate whether the dynamics are bounded or unbounded, biotically or abiotically regulated, stochastic or ecologically deterministic. Location: Worldwide. Time period: 150 Myr. Major taxa studied: Mammals. Methods: Integrating the newest phylogenetic and distributional data by means of several distinct methods, we study the ecology of mammalian diversification within a predictive framework, inspired by classic theory. Specifically, we evaluate the effects of several classes of factors, including climate, topography, geographical area, rates of climatic‐niche evolution, and regional coexistence between related and unrelated species. Next, we determine whether the relative effects of these factors change systematically across clades representing different phylogenetic scales. Results: We find that young clades diversify at approximately constant rates, medium‐sized clades show diversification slowdowns, and large clades are mostly saturated, suggesting that diversification dynamics change as clades grow and accumulate species. We further find that diversification slowdowns intensify with the degree of regional coexistence between related species, presumably because increased competition for regional resources suppresses the diversification process. The richness at which clades eventually saturate depends on climate; clades residing in tropical climates saturate at low richness, implying that niches become progressively densely packed towards the tropics. Main conclusions: The diversification process is influenced by a variety of ecological factors, whose relative effects change across phylogenetic scales, producing scale‐dependent dynamics. Different segments of the same phylogeny might therefore support seemingly conflicting results (bounded or unbounded, biotically or abiotically regulated, stochastic or ecologically deterministic diversification), which might have contributed to several outstanding controversies in the field. These conflicts can be reconciled, however, when accounting for phylogenetic scale, which might, in turn, produce a more integrated understanding of global diversity dynamics.